2018
DOI: 10.1002/app.46116
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐doped graphene as an alternative to ecotoxic zinc oxide in rubbers

Abstract: Zinc oxide (ZnO) is an essential ingredient in industrial rubber production; it regulates the onset of vulcanization, accelerates the kinetics of vulcanization, and improves the mechanical properties of rubber. However, environmental pollution with ZnO is a concern because it is recognized to be significantly ecotoxic and might also have adverse effects on human health. One of the major sources of ZnO environmental pollution is rubber items, tires in particular. Nitrogen (N)-doped graphene is a promising nextg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…There are literature studies that report that the element ZnO exhibits similar behavior in sulfur and increases the crosslink density. 57,58 In a study, it was seen that there were increases in the hardness values of compounds whose crosslink density increased, as in this study. 59…”
Section: Resultssupporting
confidence: 71%
“…There are literature studies that report that the element ZnO exhibits similar behavior in sulfur and increases the crosslink density. 57,58 In a study, it was seen that there were increases in the hardness values of compounds whose crosslink density increased, as in this study. 59…”
Section: Resultssupporting
confidence: 71%
“…The main ones include other metal oxides, 8,9 nano-sized ZnO, 10,11 zinccontaining particles, 12,13 and amine-containing complexes. 14,15 Bindu Panampilly et al 11 suggested that nano-ZnO, when used as an activator, has an elevated specific surface area and reacts more readily with stearic acid and accelerator to form zinc-accelerator complexes, accelerating the vulcanization process. The pioneering use of aminosilanes for the surface modification of SiO 2 by Silvia Mostoni et al 12 and the concomitant Zn(II) ions through modified amino the coordination was carried out, constituting a central group of Zn (II) anchored using NO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have explored intensively to reduce the amount of ZnO in rubber materials and find environmentally safe alternatives to ZnO. The main ones include other metal oxides, 8,9 nano‐sized ZnO, 10,11 zinc‐containing particles, 12,13 and amine‐containing complexes 14,15 . Bindu Panampilly et al 11 suggested that nano‐ZnO, when used as an activator, has an elevated specific surface area and reacts more readily with stearic acid and accelerator to form zinc‐accelerator complexes, accelerating the vulcanization process.…”
Section: Introductionmentioning
confidence: 99%